(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe breakfast habits and examine the association between breakfast skipping and cognitive impairment as well as nutritional status among older adults in some coastal communes of Hue City. Subjects and methods: A cross-sectional study was conducted among 489 older adults in some coastal communes of Hue City from November 2025 to March 2026. Multivariable logistic regression analysis was performed to identify factors associated with cognitive impairment and nutritional status among older adults. Results: Among 489 older adults participating in the study, 17.2% skipped breakfast. More than 80% were malnourished or at risk of malnutrition. A total of 26.6% had cognitive impairment at different levels. In the multivariable logistic regression model, breakfast skipping, older age, female sex, and lower educational level were associated with cognitive impairment. No statistically significant association was found between breakfast skipping and nutritional status in this study. Conclusion: Breakfast skipping remains fairly common among older adults in the coastal area of Hue City and is associated with cognitive impairment. These findings suggest that breakfast habits should be considered in community-based health management for older adults, particularly in coastal areas.